A summary of standards and practices for wet waste streams used in waste-to-energy technologies in the United States. (January 2020) - Badgett, Alex; Milbrandt, Anelia
Abstract: This study identifies practices and regulatory standards that pertain to the handling and disposal of wet waste materials in the United States, and summarizes these practices for the following resources: (1) food waste, (2) fats, oils and greases, (3) sewage sludge, and (4) animal manure. It outlines the standards promulgated for the wet waste materials considered herein and how these standards influence the materials' feasibility for use in waste-to-energy processes. Waste-handling standards in the United States are also briefly contrasted with disposal practices in other countries and regions. This study finds that the environment for each of the four materials is extremely variable across geographic areas not only in the United States, but also across other countries and regions. Waste markets are in various stages of development worldwide, partially due to differences in waste management standards and practices, and differences in the adoption and effectiveness of overall waste management systems. Except for several types of fats, oils, and greases, all of the resources considered here are conventionally viewed and handled as waste resources rather than commodities. However, with maturation of conversion technologies that can fully utilize these materials in advanced waste-to-energy processes, the market value of these wastes could increase. In the developing waste-to-energy industry, there could be a synergy of regulatory programs and developing markets contributing to how the wastes are managed. Where these materials are currently used in mature waste-to-energy technologies (e.g., anaerobic digestion and incineration), there exists a demonstrated example of how the materials' energy potential can be further realized while operating within the existing framework of disposal standards. Graphical abstract: Image 1 Highlights: Current practices and disposal standards for wet waste materials are summarized. Standards are reviewed from the perspective of advanced waste-to-energy pathways. Regulatory standards drive how wastes are managed and disposed. Disposal standards for all wet waste materials exhibit spatial variability. Diverting material to waste-to-energy processes must continue regulatory compliance.